2000
DOI: 10.1111/j.1744-7429.2000.tb00454.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Where to Dump the Refuse: Seed Banks and Fine Roots in Nests of the Leaf‐Cutting Ants Atta cephalotes and A. colombica1

Abstract: The location of the nutrient‐rich organic refuse produced by a leaf‐cutting ant colony varies among ant species. Atta cephalotes locate their organic refuse in subterranean chambers, whereas A. colombica place their organic refuse on the soil surface near the nest. We studied the effect of the absence or presence of external organic refuse on the abundance of fine roots and seed bank composition in the superficial horizons of ant nests. We sampled soils from ant nests or dumps and adjacent areas of 15 adult ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 23 publications
1
41
0
2
Order By: Relevance
“…Among 16 Atta species, nine inhabit this ecosystem (Fowler & Claver 1991). Fruit and seed harvesting by LCAs have been reported for dozens of tree and shrub species in neotropical forests (Nepstad et al 1990, Dalling & Wirth 1998, Farji-Brener & Medina 2000, Pizo & Oliveira 1998, Varela & Perera 2003, most of them showing features associated with primary seed dispersal by vertebrates (e.g., arillate seeds, fleshy fruits). Despite the fact that LCAs have been well-recognized as potential seed dispersers detailed quantitative studies on the extent and plant demographic consequences of this behaviour are still scarce (Dalling & Wirth 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 16 Atta species, nine inhabit this ecosystem (Fowler & Claver 1991). Fruit and seed harvesting by LCAs have been reported for dozens of tree and shrub species in neotropical forests (Nepstad et al 1990, Dalling & Wirth 1998, Farji-Brener & Medina 2000, Pizo & Oliveira 1998, Varela & Perera 2003, most of them showing features associated with primary seed dispersal by vertebrates (e.g., arillate seeds, fleshy fruits). Despite the fact that LCAs have been well-recognized as potential seed dispersers detailed quantitative studies on the extent and plant demographic consequences of this behaviour are still scarce (Dalling & Wirth 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Four aspects of this whole process have been poorly described in the literature and differ from regular foraging behaviours in Atta, including other populations of A. sexdens: (1) ant foraging via subterraneous galleries targeted to the seed sources; (2) massive seed disposal around gallery entrances subsequent to the aril removal inside the galleries; (3) short-distance seed dispersal around parental trees; and (4) regular and massive seedling cutting in seedling clumps around gallery entrances. Atta species usually (1) forage on seeds via aboveground trails (Farji-Brener & Silva 1996, Dalling & Wirth 1998; (2) carry seeds to nests far away from parental plants and lose significant numbers of them during the transport along the extended foraging trails (Lugo et al 1973, Leal & Oliveira 1998, Wirth et al 2003; and (3) discard seeds in subterraneous or external refuse dumps (Peternelli et al 2003, Farji-Brener & Medina 2000. Our findings represent new aspects of seed foraging in LCAs and extend our understanding about plasticity and opportunistic foraging of LCAs as highlighted by Rockwood and Hubbell (1987), and Kost et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in addition to their intense herbivory, leaf-cutting ant nests can change the soil texture and penetrability (Moutinho et al 2003), change the light environment by forming upside-down gaps (Farji-Brener & Illes 2000;Hull-Sanders & Howard 2003), remove competition (Coutinho 1982) and provide high nutrient concentrations in their nest refuse pit or external pile (Haines 1975(Haines , 1983Farji-Brener & Silva 1995;Farji-Brener & Ghermandi 2000;Moutinho et al 2003). A previous study noted a lack of correlation between proximity to the nest and growth rates measured as tree trunk diameter increment rates (Moutinho et al 2003), whereas others have observed a proliferation of roots in abandoned nest and nest refuse chambers and piles (Haines 1978;Carvalheiro & Nepstad 1996;Farji-Brener & Medina 2000;Moutinho et al 2003). These seemingly ambiguous results may be due in part to the observation that proximity to the nest is a poor indicator of nest nutrient resource utilization as evidenced by our study showing several plant individuals close to the nest that did not acquire nest nutrients.…”
Section: (D) Broader Implicationsmentioning
confidence: 99%
“…Analyses of the nest refuse and soils associated with leaf-cutting ant nests showed a substantially greater concentration of macronutrients and soil penetrability relative to non-nest soils (Haines 1975(Haines , 1983Farji-Brener & Silva 1995;Farji-Brener & Ghermandi 2000;Moutinho et al 2003). Excavations in neo-tropical forests show that there is an abundance of plant roots in abandoned subterranean leaf-cutting ant nest trails and pits (Haines 1978;Carvalheiro & Nepstad 1996;Farji-Brener & Medina 2000;Moutinho et al 2003), which may have an important effect on the overall distribution of roots in the soil profile (Sternberg et al 1998). Even in active nests, coarse and fine roots exploit deeper layers of the soil profile (greater than 6.0 m) and are more prolific in nestassociated soils (Moutinho et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation